Pembentukan GELAS KACA (Gerakan Lansia Kelola, Adaptasi, Cegah dan Tangguh) Selama Pandemi Covid-19 - Dewi Nurviana Suharto; Dafrosia Darmi Manggasa (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The increase in the number of COVID-19 cases took place quite quickly, and spread to various districts in Indonesia in a short time including Poso Regency. The elderly and those with comorbidities are at risk of contracting and experiencing worse complications due to COVID-19. Therefore, it is very important to prevent transmission through promotive and preventive efforts to the elderly, both at the family, community and health facilities levels. To achieve this, one of them is through the establishment of GELAS KACA (Gerakan Elderly Manage, Adapt, Prevent and Resilient), which aims to increase the knowledge of the elderly in preventing the transmission of COVID-19. The problems that the elderly do not know how to manage illness during the pandemic, the elderly feel stressed because they have to stay at home, only health services are carried out if it is really important, the observation results show that there are also some elderly people who are afraid to go to health services for fear of being diagnosed with COVID -19. This is the basis for the implementation of the service which aims to establish GELAS KACA (The Elderly Movement for Managing, Adapting, Preventing and Resilient). The service is carried out by providing education on preventing COVID-19 transmission, self-management, adapting new habits and stress management, then evaluating the knowledge of the elderly after being given education. The results of the service showed that knowledge increased to 95%, psychosocial problems obtained were neurosis symptoms as much as 100%.